(untitled) (Archives of Criminology, 2002)
The article presents the results of survey research carried out in the Katowice and Chorzów regions (SE Poland). In early 2000 we obtained 414 questionnaires completed by under- and post-graduate students at the University of Silesia’s Law and Administration Department and students of local high schools. The investigation was victimology-oriented, the respondents being asked not only whether they had been victims of crime of various kinds but also whether the perpetrator had been punished. Our premise was that based on measures adopted by Polish criminal procedure the victim of a crime was entitled to know of the offender’s punishment, assuming that he had in fact been convicted. Within our sample the predominant group was young people, females marginally outnumbered males, almost all respondents reported average or above-average circumstances, and almost all were also urban–dwellers, the vast majority living in towns with populations of over 100,000. The first question that interested us was the effectiveness of the law, chich is most fully reflected in measurements of absolute effectiveness, that is, the percentage of crimes punished to the total number of crimes actually committed. This umounted to 3.33%. If we deduct the relatively large number of non-indictable offenses, i.e. not subject to prosecution by the state (e.g. libel and slander) the figure rises to 4.02%. In addition to the absolute effectiveness measure we also calculated a relative effectiveness index. It was the ratio of punished offenses to the total number of offenses reported to law-enforcement authorities by the respondents. In our survey the relative effectiveness index amounted overall to 20.0% and after the elimination of non-indictable offenses to 19.7%. To estimate effectiveness we deducted offenses committed in 1999 on the assumption that the majority of these were too recent for prosecution and conviction to have taken place. Obviously, a crucial influence on measurement of the effectiveness of the law is exerted by the number of offenses reported to law-enforcement authorities. Our questionnaire was designed to allow respondents to adduce the number of instances of victimization in the preceding year and in general without mentioning their location in time. Since the survey was carried out in earlv 2000 the preceding year was 1990. The level of notification of crimes for the whole period in question came in our survey to 15.3% of the total incidence of crime. For 1999 this ratio recorded a count of 13.1% in other words was fractionally lower. After deducting non-indictable offenses these indexes rise to 19.9% and 19.0 % respectively. The most frequently reported crimes were burglaries (58.7%). Next on the list came simple larceny (18.6%) and fraud (18.1%, 29.5% in 1999); no cases of bribery were reported. A relatively rarely reported crime was robbery with violence (12.2%, 13.7% in 1999). The so-called "dark figure" can be stated in a variety o ways. One is by an absolute number, either broader or narrower. This depends on inclusion in the dark figure of all offenses actually committed or only those which are not reported to the law-enforcement authorities or are subject to private prosecution. Another way of determining the dark figure is by an index- or ratio-based measure. Here, too, there are two possibilities. In the first the number of offenses actually committed per the number punished is calculated. The second estimates the number of offenses actually committed per the number reported. The findings of our survey were as follows. The dark figure for the total number of crimes actually committed and the whole of the period in question amounted in absolute terms to 1,492 and for unreported offenses to 1,263. For 1999 corresponding counts came to 562 and 488 respectively. In index-measured terms the number of offenses actually committed per the number reported amounted for the whole period in question to 6.5 and for 1999 to 7.6, in other words to fractionally more. The number of offenses actually committed per the number punished (after deducting offenses committed in 1999) since it is hardy likely that any of these would already have been punished in early 2000 amounted to 30. Considerable attention was given to determining the structure of offenses committed, reported and punished and to the structure of offenses committed to the injury of different categories of victims (men, women, high school students, undergraduates, doctoral students). Differences were found here. The most significant was that the most frequent victims of offenses against the person are males and persons in the younger age group; the same pattern holds for robberies with violence of which females are only exceptionally the victims (only three cases in the whole the of the material gathered by the survey). By contrast, females and persons in the older age group are the most frequent victims of simple larceny. An in-depth victimologicar analysis yielded the following findings. The coefficient of victimization, that is, the total number of offenses per member of the sample, amounted for the totality of our respondents over the whole period in question to 3.60, though it was much higher for the male and younger age group (5.5 for the former and 7.86 for the fourth-year high school students). In the females group as a whole the coefficient came to 2.40 and was highest in the doctoral students sub-group (3.27). The victimization index is the percentage of the number of crime victims in the whole of the sample. If we subtract the victimization index from 100 we will obtain a percentage measure of the number of persons who have not be victims either of any crime or of a crime of particular kind. For the whole of the sample and the whole of the period in question this index amounted to 76.1%, i.e. the number of non-victimized persons did not exceed 23.9%; for 1999 the counts were 47.1% and 52.9% respectively. The victimization index in the males group amounted to 85.1% for the whole period in question and to 57.8% for 1999; in the females group the analogous counts came to 70,4% and 40.3% respectively. Victimization intensity is a measure which is characterized by the number of criminal acts committed per victim. In our survey it amounted to 4.74 for the whole sample and the whole period covered by the survey and to 2.88 for 1999. The analogous scores for the males and females group came to 6.46 and 3.68 and for the females to 3.41 and 2.16. An important supplement to victimological investigation is determining an index of victimization variation. It completes the picture provided by victimization intensity. For obvious reasons this measure is calculated only for the whole sample or its subgroup. It illustrates how many kinds of offenses have been committed against the average victim. Victimization variation is calculated by dividing the sum of the number of individuals wronged by particular categories of offenses by the total number of victims among the persons included in the sample. There is a certain relationship between victimization intensity and variation. If intensity equals one, variation also equals one. Aside from this instance variation either equals intensity or is slightly lower. Variation can never exceed the number of the kinds of offenses specified in an investigation. Within these limits the closer the variation index is to the value of variation, the higher the variation of criminality given that intensity is relatively high. If inteisity approaches unity variation, despite the proportionately high level of the index, diminishes. In our survey intensity for the whole group and for the whole period in question amounted to 4.74 and for 1999 to 2.88. In other words, the average number of offenses per victim came overall to almost five, and in 1999 this average came to close on three.The variation measures attained a level of, respectively, 2.38 and 1.58 which means that, overall, victims were wronged on average by two kinds of offenses and in 1999 by between one and tow. The highest intensity occurred in the males subgroup of the high school students group (8.24) which also had the highest variation index (3.46). As for intensity second place was occupied by males in the doctoral students group (8.04), thougt its variation score/count was markedly lower than in the high school students group (2.80). Our survey also indicated the scale of drug abuse. The respondents were asked to state the number of contacts they had had with persons using drugs and with dealers or producers of drugs. Within the whole group studied contacts with consumers of drugs were reported by 49.0% of the respondents and contacts with drug dealers or producers by 25.1%. These contacts were much more frequent among the high school students (67.4% and 39.3% respectively) than among tne undergraduates and doctoral students (27.4% and 8.6%). The survey presented here covered a relatively small group of persons and one drawn from only a single region. Further investigations of this type are essential.